Survival benefit with checkpoint inhibitors versus chemotherapy is modified by brain metastases in patients with recurrent small cell lung cancer - Althoff, Friederike C.; Schäfer, Lisa V.; Acker, Fabian; Aguinarte, Lukas; Heinzen, Sophie; Rost, Maximilian; Atmaca, Akin; Rosery, Vivian; Alt, Jürgen; Waller, Cornelius F.; Reinmuth, Niels; Rohde, Gernot; et al. (Frontiers in Oncology, 2023)
Introduction: Small cell lung cancer (SCLC) is a rapidly growing malignancy with early distant metastases. Up to 70% will develop brain metastases, and the poor prognosis of these patients has not changed considerably. The potential of checkpoint inhibitors (CPI) in treating recurrent (r/r) SCLC and their effect on brain metastases remain unclear.In this retrospective multicenter study, we analyzed r/r SCLC patients receiving second or further-line CPI versus chemotherapy between 2010 and 2020. We applied multivariable-adjusted Cox regression analysis to test for differences in 1-year mortality and real-world progression. We then used interaction analysis to evaluate whether brain metastases (BM) and/or cranial radiotherapy (CRT) modified the effect of CPI versus chemotherapy on overall survival.Results: Among 285 patients, 99 (35%) received CPI and 186 (65%) patients received chemotherapy. Most patients (93%) in the CPI group received nivolumab/ipilimumab. Chemotherapy patients were entirely CPI-naïve and only one CPI patient had received atezolizumab for first-line treatment. CPI was associated with a lower risk of 1-year mortality (adjusted Hazard Ratio [HRadj] 0.59, 95% CI 0.42 to 0.82, p=0.002). This benefit was modified by BM and CRT, indicating a pronounced effect in patients without BM (with CRT: HRadj 0.34, p=0.003; no CRT: HRadj 0.50, p=0.05), while there was no effect in patients with BM who received CRT (HRadj 0.85, p=0.59).CPI was associated with a lower risk of 1-year mortality compared to chemotherapy. However, the effect on OS was significantly modified by intracranial disease and radiotherapy, suggesting the benefit was driven by patients without BM.